2009
DOI: 10.1002/term.143
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and functional comparison of optimum culture conditions for upscaling of bone marrow-derived mesenchymal stem cells

Abstract: Human adult bone marrow-derived mesenchymal stem cells (MSCs) are a promising tool in the newly emerging avenue of regenerative medicine. MSCs have already been translated from basic research to clinical transplantation research. However, there is still a lack of consensus on the ideal method of culturing MSCs. Here we have compared different culture conditions of human MSCs with an attempt to preserve their characteristics and multi-lineage differentiation potential. We compare the different basal culture med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
78
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 18 publications
7
78
0
Order By: Relevance
“…33 Our data showed that nearly 95% of the articles described the culture medium used for DPSCs (Table 1), indicating a very low risk of bias and therefore highlighting the relevance of this factor. Nineteen different types of culture medium were cited.…”
Section: Discussionmentioning
confidence: 66%
“…33 Our data showed that nearly 95% of the articles described the culture medium used for DPSCs (Table 1), indicating a very low risk of bias and therefore highlighting the relevance of this factor. Nineteen different types of culture medium were cited.…”
Section: Discussionmentioning
confidence: 66%
“…al 2012. However, to avoid the potential risk of exposing human patients to cells cultivated in the presence of FBS, some investigators have searched for a substitute supplement (Bieback et al 2009) because, according to the results of Pal et al (2009), the presence of serum is essential for maintaining and expanding mesenchymal stem cell cultures. In the present work, despite samples coming from adipose tissue, they showed greater cellularity in DMEM supplemented with FBS in the first two weeks, but afterwards, there is no longer any difference in relation to grown in AIM-V medium without FBS, suggesting that this can be an alternative for the culture of cells destined for transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…85 To account for these contradictory reports, it is hypothesized that improved transmission in intact fibers subserving the zone of partial preservation leads to early improvements. 86 Another possible explanation is the source, 87,88 culture conditions, and passage number [89][90][91][92] of the mesenchymal stem cells used, as all are known to influence mesenchymal stem cell potential. A third possible explanation is differential efficacy of mesenchymal stem cells from different donors.…”
Section: Amr Et Al Bridging Defects With Nerve Grafts and Stem Cellsmentioning
confidence: 99%